BUY BYTE (CIPEEX, 2025)
Buy Byte, an online platform that facilitates the resale of used computers andperipherals, emerges as a sustainable solution to combat the growing issue ofplanned obsolescence and the improper disposal of electronic equipment.To evaluate the platform's effectiveness in promoting the circular economy anddemocratizing access to technology, the study combined quantitative andqualitative data.The results show that Buy Byte meets the increasing demand for financiallyaccessible and sustainable technological solutions. It offers a secure andintuitive environment where users looking to upgrade their devices can findmore affordable options.The platform stands out by providing detailed technical information aboutproducts, guiding the proper disposal of electronics, and fostering the exchangeof experiences and information among users through an interactive forum.Buy Byte represents a viable solution for sustainable technology consumptionand the circular economy, with potential for expansion in terms of productofferings and complementary services.
Keywords: buyb